Conclusions and policy implications - Hyde, William F.; Jintao Xu; Belcher, B.; Runsheng Yin; Jinlong Liu (Resources for the Future and Center for International Forestry Research, 2003)
This final chapter reviews the findings of the empirical chapters, summarizes authors observations for China, and explains these observations within the context of global forest policy. The institutions that define land tenure and the means of delivering tenurial rights is one great theme of China's experience--and this book. The impacts of spillovers from policy reform in other sectors and from general economic growth is another. It also reflects on those new issues that arose subsequent to the analyses of the other chapters and those additional issues that are becoming important only now, in the twenty-first century. Forest environmental issues are particularly complex. Finally, tenure continues to be an issue, sometimes with a distributive theme, sometimes with an efficiency theme. Restrictions on household harvest and shipments as well as high levels of forest taxation continue to constrain household forestry incentives. The central government recognizes these issues, but local administratiors will largerly determine whether future growth in China's forestry sector is characterized by imports and product substitution or by domestic production.